Chemotherapy for cervical cancer and contraception: discussion issues and clinical case - E. A. Ulrikh; V. G. Borshchevskiy; I. S. Zakharov; A. A. Bezmenko; D. I. Gayvoronskikh; A. V. Prichina; A. S. Saykina; A. K. Bairova (Опухоли женской репродуктивной системы, 2024)
Cervical cancer occupies one of the leading places in the structure of oncological diseases of the Female Reproductive System. In the treatment of this pathology, along with the surgical method of treatment, chemotherapy and radiation therapy are used. According to clinical guidelines, in the presence of cervical cancer stages IIB–IIIA, it is allowed to carry out 2–4 cycles of neoadjuvant chemotherapy in order to create conditions for the possibility of performing extended hysterectomy according to Meigs. Pregnancy during chemotherapy is unique and extremely rare.The article presents a clinical case of pregnancy during chemotherapy (performed according to the scheme: taxanes and platinum-containing drugs) in a 27-year-old patient. According to the clinical picture and results of cervical biopsy, the diagnosis was made: invasive nonkeratinizing squamous cell carcinoma of the cervix IIB (cT2bNxM0) G2, right-sided parametric variant, nonspecific (with unspecified HPV status). Taking into account the presence of parametrial infiltration, the age of the patient, the oncological council prescribed from 2 to 4 cycles of chemotherapy according to the TC scheme (paclitaxel, carboplatin) with an interval assessment. After the second cycle of chemotherapy, an early pregnancy was diagnosed – a medical abortion was performed. Against the background of 3 cycles of chemotherapy, the conditions for surgical treatment were formed – surgical treatment was performed in the amount of extended hysterectomy according to Meigs (type III according to Piver/C2 Morrow) with transposition of the ovaries. The postoperative period was uneventful; the patient was discharged in a satisfactory condition.The described case of pregnancy on the background of chemotherapy is of scientific and practical interest, initiating a discussion on the need to counsel such patients regarding reliable contraception, taking into account the eligibility criteria, which will avoid undesirable outcomes during cancer treatment.